Detecting the role of Stokes drift under typhoon condition by a fully coupled wave-current model - Yu, Ting; Deng, Zengan; Zhang, Chi; Hamdi Ali, Amani (Frontiers in Marine Science, 2024)
The impacts of Stokes drift and sea-state-dependent Langmuir turbulence (LT) on the three-dimensional ocean response to a tropical cyclone in the Bohai Sea are studied through two-way coupled wave-current simulations. The Stokes drift is calculated from the simulated wave spectrum of the wave model, Simulating Waves Nearshore (SWAN), and then input to the Princeton Ocean Model with the generalized coordinate system (POMgcs) to represent the Langmuir effect. The Langmuir circulation is included in the vertical mixing of the ocean model by adding the Stokes drift to the shear of the vertical mean current and by including LT enhancements to the Mellor-Yamada 2.5 turbulent closure submodel. Simulations are assessed through the case study of Typhoon Masta in 2005 with a set of diagnostic experiments that incorporated different terms of Stokes production (SP) respectively. It is shown that with the consideration of SP, a deeper mixed layer, an enhanced vertical mixing coefficient KMS, and a more accurate representation of the vertical temperature distribution could be derived. Moreover, the effect of LT in elevating the turbulence mixing is stronger than that of Coriolis Stokes force (CSF) and Craik-Leibovich vortex force (CLVF). LT has a greater influence on the vertical mixing during typhoon than that in normal weather.